2020
DOI: 10.13106/jafeb.2020.vol7.no8.425
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Motivational Factors on the Work Results of Lecturers at Vietnam National University, Hanoi

Abstract: This paper aims to develop a conceptual framework for evaluating the impact of motivational factors on the work results of lecturers at Vietnam National University, Hanoi (VNU), one of two leading multidisciplinary and multi-sectoral national universities in Vietnam. This study has considered wages and other benefits (WB), training and development (TD), working environment (WE) and working motivation (WM) as motivational factors, and proposed a structural model of the impact of motivational factors on the work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…The geometric mean method by Buckley [46] was used to calculate each factor in the comparison matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometric mean method by Buckley [46] was used to calculate each factor in the comparison matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a technical support process was developed to evaluate lecture performance, applying a new dynamic fuzzy technique for order preference by similarity to ideal solution (DFTOP-SIS). The university functions as both a training facility and a scientific research center, encouraging lecturers to undertake scientific research activities [46]. Do et al [47] proposed an extension of the generalized fuzzy multicriteria decision-making (MCDM) approach to evaluate a lecturer's research capacity.…”
Section: Research On Knowledge Management In Universitiesmentioning
confidence: 99%
“…This result is not in accordance with previous studies. conducted by several previous studies show that motivation affects performance as the results of research(Kolk, Berend Van Der, 2019), (Miao et al, 2019), (Do et al, 2020), (Hutagalung, Riama Katarina, 2020), (Petrovsky et al, 2014), (Usman, 2017) Several related studies were used as references in this study, including research conducted by (Kolk, Berend Van Der, 2019) in subsequent studies explained that employee motivation plays one of the most important parts in organizational performance and confidently contributes to its development and prosperity. This unaffected result shows that for school principals as leaders in school organizations, the motivational factor is not a concern for principals to support the achievement of good accountability.…”
Section: H2: There Is An Influence Of Motivation Onaccountabilitymentioning
confidence: 93%
“…Based on the previous explanation, it is known that accountability is a form of performance appraisal, so the concept of accountability uses the basic concept of performance, thus some previous studies that are used as references by researchers are research related to motivation towards performance. In general, several previous studies have shown that motivation has an effect on performance, such as the results of research (Kolk, Berend Van Der, 2019), (Miao et al, 2019), (Do et al, 2020), (Hutagalung, Riama Katarina, 2020), (Petrovsky et al, 2014), (Usman, 2017) Several related studies were used as references in this study, including research conducted by (Kolk, Berend Van Der, 2019) in subsequent studies explained that employee motivation plays one of the most important parts in organizational performance and confidently contributes to its development and prosperity. In this way, it is very important for every entrepreneur and manager to find out what really convinces employees to work hard and how to maximize organizational performance in general.…”
Section: The Need For Affiliatementioning
confidence: 96%
“…Employees who are motivated to a high degree are required in today's dynamic workplace environment. Motivated workforce unceasingly contributes to the organizational flourishment and survival because a motivated workforce helps enhance organizational productivity and enables an organization to attain greater level of production (Do et al, 2020). Still, motivating the workforce is possibly the most intricate and entangled matter that the business managers are encountering in recent times.…”
Section: Introductionmentioning
confidence: 99%